If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10c + -9c = 6 Combine like terms: 10c + -9c = 1c 1c = 6 Solving 1c = 6 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '1'. c = 6 Simplifying c = 6
| z^2+12z=20 | | -5(x-2)-3x=2-(-8+3x) | | 3p-2= | | 7x-(3x+11)=-6(5-3x) | | -x+64=5x-14 | | 9t-3t-5t-2t-4t=18 | | 25x^2-30x+21=0 | | 8x-13=35 | | 4y^4-37y^2+9=0 | | 6r+3=3r-27 | | C=5x+770 | | 7c*2p+3-8=6p+29 | | (7x+3)=2 | | 16s+4s=20 | | 9n-37=71 | | 3h-h=10 | | 2(x+9)=20 | | 9m-6m=6 | | 10w-4w=18 | | (x+3y)(3x+y)= | | (1+2w)*w*2w=40 | | -60x^3+144x= | | c/4+85=99 | | 4x+1=6-x | | -4+6s+7m-4s-4m-6= | | 2(13-4x)-9(x+6)= | | 49x^2-91+42=0 | | -8x-(5x+5)=7 | | 2(h-4)=6 | | 3y+7(2y+6)-2+3(4y+9)=270 | | -7x-15=2x-6 | | 12a-11-9a=1 |